2022
DOI: 10.1111/ggi.14508
|View full text |Cite
|
Sign up to set email alerts
|

Impact of number of functional teeth on independence of Japanese older adults

Abstract: Aim To examine the relationship between the number of present and functional teeth at baseline and future incidence of loss of independence. Methods Participants were community‐dwelling older individuals who participated in a comprehensive geriatric health examination conducted in Kusatsu town, Japan, between 2009 and 2015. The primary endpoint was the incidence of loss of independence among participants, defined as the first certification of long‐term care insurance in Japan. The numbers of present and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…As expected, the results indicated that the number of present and functional teeth were not significant risk factors for mortality in the study population. In contrast, previous studies targeting healthy community-dwelling older adults [4,5,31,32] or those requiring nursing care have indicated a positive association between tooth loss (present and functional teeth) and mortality [33,34]. However, in agreement with our results, Saarela et al suggested that the teeth present were not risk factors for mortality among older adults residing in nursing care facilities, as estimated by Cox regression analysis adjusted for age, sex, comorbidities, and MNA scores [18].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As expected, the results indicated that the number of present and functional teeth were not significant risk factors for mortality in the study population. In contrast, previous studies targeting healthy community-dwelling older adults [4,5,31,32] or those requiring nursing care have indicated a positive association between tooth loss (present and functional teeth) and mortality [33,34]. However, in agreement with our results, Saarela et al suggested that the teeth present were not risk factors for mortality among older adults residing in nursing care facilities, as estimated by Cox regression analysis adjusted for age, sex, comorbidities, and MNA scores [18].…”
Section: Discussionsupporting
confidence: 83%
“…Subsequently, Kaplan-Meier estimator analysis was performed to calculate the participants' cumulative survival rate by sex (male or female), BI score (<40 or ≥40) [26], BMI (underweight or others), nursing care environment (residential care/home care), food texture (regular/modified), number of present teeth (<10, 10-19, or ≥20) and number of functional teeth (<20 or ≥20) [4,5]. Log-rank tests were used to compare the survival curves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The masticatory function of partially or totally edentulous individuals can be recovered to some degree by replacing missing teeth [4,5]. The number of functional teeth, including remaining natural teeth and prosthetically restored missing teeth [6][7][8], is widely used in the field of oral epidemiology as an index of oral health when considering dental prosthetic treatments. Two well-designed, large-scale cohort studies [7,8] reported that a lower number of functional teeth was associated with an increased risk of disability and mortality.The possible underlying mechanisms for the association be-tween a lower number of functional teeth and diminished healthy longevity include inadequate and poor-quality diets induced by poor oral health and function [2,3].…”
mentioning
confidence: 99%
“…The number of functional teeth, including remaining natural teeth and prosthetically restored missing teeth [6][7][8], is widely used in the field of oral epidemiology as an index of oral health when considering dental prosthetic treatments. Two well-designed, large-scale cohort studies [7,8] reported that a lower number of functional teeth was associated with an increased risk of disability and mortality.…”
mentioning
confidence: 99%